Front Cover: Whole Agrocybe cylindracea Prevented Obesity Linking with Modification of Gut Microbiota and Associated Fecal Metabolites in High‐Fat Diet‐Fed Mice. Issue 7 (3rd April 2022) - Zhu, Zhenjun; Huang, Rui; Liu, Wei; Wang, Juan; Wu, Shujian; Chen, Mengfei; Huang, Aohuan; Xie, Yizhen; Chen, Moutong; Jiao, Chunwei; Zhang, Jumei; Wu, Qingping; et al.
Abstract : Mol. Nutr. Food Res . 2022, 66, 202100897 DOI: 10.1002/mnfr.202100897 Dietary Agrocybe cylindracea (AC) can beneficially modulate the gut microbiota and associated metabolites in HFD‐fed mice. The beneficial effects of AC have been identified to significantly correlate with its prevention of diet‐induced obesity and its complications. This is reported by Yu Ding and co‐workers in article number 2100897 .